2015
DOI: 10.1002/1873-3468.12033
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Maf1 enhances pyruvate kinase activity and fermentative metabolism while influencing lipid homeostasis in Saccharomyces cerevisiae

Abstract: Edited by Judit OvadiThe Maf1 protein is a general negative repressor of RNA polymerase III, which is conserved in eukaryotes from yeast to humans. Herein, we show the yeast maf1D mutant increases pyruvate kinase activity, the key enzyme in glycolysis and an important player in switching between fermentative and oxidative metabolism. We observed enhanced ethanol production and elevated lipid content in the maf1D strain grown on glucose. However, after shifting to a non-fermentable carbon source, the opposite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(36 reference statements)
3
8
0
Order By: Relevance
“…Similarly, mafr-1 (KO) animals displayed increased intracellular lipid abundance relative to age-matched WT control animals ( Fig. 1E), as expected from previous studies (Khanna et al, 2014;Mierzejewska and Chreptowicz, 2016;Palian et al, 2014;Pradhan et al, 2017). Our previous investigations revealed that overexpression of mafr-1 can influence reproductive output (Khanna et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Similarly, mafr-1 (KO) animals displayed increased intracellular lipid abundance relative to age-matched WT control animals ( Fig. 1E), as expected from previous studies (Khanna et al, 2014;Mierzejewska and Chreptowicz, 2016;Palian et al, 2014;Pradhan et al, 2017). Our previous investigations revealed that overexpression of mafr-1 can influence reproductive output (Khanna et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Since rpc128-1007 grows poorly at high concentration of extracellular glucose (2%) we hypothesized that there was a lower glycolysis efficiency in the strain compared with the wild-type and maf1-Δ which in contrast displays growth inhibition on a non-fermentable carbon source but seems to metabolize glucose very efficiently when glucose is present at high concentrations [ 49 ], [ 82 ]. We verified energy status in the strains by measuring invertase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Since these early studies, subsequent work in yeast has revealed that loss of Maf1 shows enlarged lipid droplets and was correlated to increased pyruvate kinase activity [18]. Moreover, a tumor suppressor function has been assigned to MAF1 [13,22], which could result from MAF1-dependent effects on lipid biosynthesis and/or RNA pol III transcription.…”
Section: Discussionmentioning
confidence: 99%